Efek Ekstrak Biji Leucaena leucocephala L. terhadap Profil Lipid Darah Tikus Diabetes - Humairoh Hanan; Syamsudin Syamsudin (JURNAL ILMU KEFARMASIAN INDONESIA, 2004)
The use of Leucaena leucochepala as an antidiabetic has already been known in society, but the support experiment was very rare. The purpose of this experiment is to know whether the extract of L. leucochepala semen have an effect to the blood lipid profile of a NIDDM rat which is streptozotocin (stz) induced. It is made in 6 groups, each group consist of 5 rats. Group 1: Normal control, group 2: Negative control (stz), group 3: Positive control (clorpropamid), group 4: Extract of Leucaena semen low dose (0.25 g/kg BW), group 5: Extract of Leucaena semen medium dose (0.5 g/kg BW) and group 6: Extract Leucaena semen high dose (1 g/kg BW). Rats are made hiperglycemia with iv induction of stz 50 mg/kg BW. Chlorpropamid and Leucaena semen extract are given orally. The experiment results of blood sugar level, total cholesterol, triglyceride, HDL and LDL are analyzed by ANOVA and continued with BNT test (p < 0.05). The result from the experiment is the high reduction of blood sugar level from the Leucaena semen extract high dose in amount of 65.30%. Results from the total cholesterol level of group 1:61.60 mg/dl, group 2: 91.60 mg/dl, group 3: 62.20 mg/dl, group 4: 76.00 mg/dl, group 5: 65.40 mg/dl and group 6: 55.80 mg/dl. Results from the triglyceride level of group 1: 83.40 mg/dl, group 2: 201.40 mg/dl, group 3: 133.40 mg/dl, group 4: 114.80 mg/dl, group 5: 93.20 mg/dl and group 6: 80.40 mg/dl. Results from the HDL level of group 1: 47.60 mg/dl, group 2: 26.40 mg/dl, group 3: 35.20 mg/dl, group 4: 43.40 mg/dl, group 5:58.40 mg/dl and group 6: 90.40 mg/dl. Results from the LDL level of group 1: -2.68 mg/dl, group 2:26.72 mg/dl, group 3: 0.32 mg/dl, group 4: 9.64 mg/dl, group 5:-11.64 mg/dl and group 6: -50.16 mg/dl.